IMPROVING CIVIL STUDY LEARNING RESULTS WITH THE COOPERATIVE LEARNING MODEL TYPE: GROUP INVESTIGATION (GI) IN MAIN MATERIALS OF VIOLATION OF HUMAN RIGHTS IN PANCASILA PErSPECTIVE IN CLASS XI, SMA NEGERI 2 AMARASI 2018 - Oni Simons Rafael (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
The purpose of this Classroom Action Research is an effort to improve student learning outcomes in Civics learning on the Main Material